Antifungal Susceptibility Patterns of Opportunistic Fungi in the Genera Verruconis and Ochroconis - Seyedmousavi, S. (American Society for Microbiology, 2014)
Species of Verruconis and species of Ochroconis are dematiaceous fungi generally found in the environment but having the ability to infect humans, dogs, cats, poultry, and fish. This study presents the antifungal susceptibility patterns of these fungi at the species level. Forty strains originating from clinical and environmental sources were phylogenetically identified at the species level by using sequences of the ribosomal DNA internal transcribed spacer (rDNA ITS). In vitro antifungal susceptibility testing was performed against eight antifungals, using the Clinical and Laboratory Standards Institute (CLSI) broth microdilution method. The geometric mean MICs for amphotericin B (AMB), flucytosine (5FC), fluconazole (FLC), itraconazole (ITC), voriconazole (VRC), and posaconazole (POS) and minimum effective concentrations (MECs) for caspofungin (CAS) and anidulafungin (AFG) across the Ochroconis and Verruconis species were as follows, in increasing order. For Verruconis species, the values (μg/ml) were as follows: AFG, 0.04; POS, 0.25; ITC, 0.37; AMB, 0.50; CAS, 0.65; VRC, 0.96; 5FC, 10.45; and FLC, 47.25. For Ochroconis species, the values (μg/ml) were as follows: AFG, 0.06; POS, 0.11; CAS, 0.67; VRC, 2.76; ITC, 3.94; AMB, 5.68; 5FC, 34.48; and FLC, 61.33. Antifungal susceptibility of Ochroconis and Verruconis was linked with phylogenetic distance and thermotolerance. Echinocandins and POS showed the greatest in vitro activity, providing possible treatment options for Ochroconis and Verruconis infections.